Structure and flexural properties of 3D needled carbon fiber reinforced carbon and silicon carbide (C/C-SiC) composites fabricated by gaseous and liquid silicon infiltration - Wan, F; Pizada, T; Liu, R; Wang, Y; Qi, G; Zhang, C; Marrow, T (Elsevier, 2019)
3D needled carbon fiber reinforced composites (C/C-SiC) were fabricated by gaseous silicon infiltration (GSI) for different reaction times, followed by further densification with liquid silicon infiltration (LSI). The density, flexural modulus and flexural strength increased as a spatially connected SiC structure developed, but the flexural strength could be degraded by a long total reaction time. The composites all exhibited quasi-brittle fracture with fiber bundle pull-out and interfacial debonding. Fracture could propagate within the needle bundles that were perpendicular to the tensile stress.